The gut microbiota-related metabolite phenylacetylglutamine associates with increased risk of incident coronary artery disease. Issue 12 (December 2020) - Ottosson, Filip; Brunkwall, Louise; Smith, Einar; Orho-Melander, Marju; Nilsson, Peter M.; Fernandez, Céline; Melander, Olle
Abstract : Objective: The gut microbiota is increasingly being implicated in cardiovascular health. Metabolites produced by bacteria have been suggested to be mediators in the bacterial action on cardiovascular health. We aimed to identify gut microbiota-related plasma metabolites and test whether these metabolites associate with future risk of coronary artery disease (CAD). Methods: Nontargeted metabolomics was performed using liquid chromatography-mass spectrometry in order to measure 1446 metabolite features in the Malmö Offspring Study (MOS) ( N  = 776). The gut microbiota was characterized using 16S rRNA sequencing. Gut bacteria-related metabolites were measured in two independent prospective cohorts, the Malmö Diet and Cancer – Cardiovascular Cohort (MDC-CC) ( N  = 3361) and the Malmö Preventive Project (MPP) ( N  = 880), in order to investigate the associations between gut bacteria-related metabolites and risk of CAD. Results: In MOS, 33 metabolite features were significantly ( P  < 4.8e-7) correlated with at least one operational taxonomic unit. Phenylacetylglutamine (PAG) was associated with an increased risk of future CAD, using inverse variance weighted meta-analysis of age and sex-adjusted logistic regression models in MDC-CC and MPP. PAG remained significantly associated with CAD (OR = 1.17, 95% CI = 1.06–1.29, P  = 1.9e-3) after adjustments for cardiovascular risk factors. Conclusion: The levels of 33 plasma metabolites were correlated with the gut microbiota. Out of these, PAG was associated with an increased risk of future CAD independently of other cardiovascular risk factors. Our results highlight a link between the gut microbiota and CAD risk and should encourage further studies testing if modification of PAG levels inhibits development of CAD. Abstract : Supplemental Digital Content is available in the text